2022
DOI: 10.1155/2022/5353889
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Influence of Public Mental Health Based on Artificial Intelligence Technology on the Teaching Effect of Business Administration Major

Abstract: As an emerging technology, public mental health based on artificial intelligence engineering has broad application and development prospects in improving teaching effects, realizing high efficiency and intelligence, and improving refined education. The application of public mental health based on artificial intelligence engineering in the practice of the teaching effect of business administration has a very positive significance for accurately discovering the mental health and teaching effect of business admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For example, machine learning-based technologies have shown promise in detecting, diagnosing, and treating depression (Squires et al, 2023). Furthermore, AI has been used in universities to improve public mental health education, raising both student and faculty awareness of mental health issues (Li et al, 2022;Lu, 2022). Therefore, this article sheds light on the use of AI in mental health care and highlights areas where advancement is possible.…”
Section: Introductionmentioning
confidence: 99%
“…For example, machine learning-based technologies have shown promise in detecting, diagnosing, and treating depression (Squires et al, 2023). Furthermore, AI has been used in universities to improve public mental health education, raising both student and faculty awareness of mental health issues (Li et al, 2022;Lu, 2022). Therefore, this article sheds light on the use of AI in mental health care and highlights areas where advancement is possible.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%